Dark Tourism: Tourist Motivations at The Site of Grief in Liberty Shrine, Cebu, Philippines - Adelan, Lucita A.; Carillo, Lovella V.; Delantar, Alexander Franco A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
There is a marked rise in the development of outrage and demise-related tourist spots, destinations, and places of interest that provide potential information, insight, and recreation, enticing individuals eager to consume natural and commoditized death. The Liberty Shrine in Mactan, Cebu, Philippines, is an example of dark tourism because this spot is a commemorative marker that gives people an insight that the place was where Chieftain Lapu-Lapu killed Ferdinand Magellan during the battle in Mactan that, makes the latter the first Filipino to have deterred European belligerence. The study aimed to identify tourist motivations at the grief site in Liberty Shrine, located at Mactan, Cebu, Philippines. The study utilized the descriptive survey method validated through in-depth interviews, documentary analysis, and historical analysis. Using Stone's (2006) Dark Tourism theory, data were obtained from one hundred respondents (100), including government employees, residents, and tourists. Results revealed that visitor motivations at the grief site included location, education, motive, and promotion. It concluded that although location and education were rated Very Effective, motive and promotion were rated Effective only. The study recommended that the site management conduct systematic research and various promotional strategies, focusing on those that have proven more effective.